Cyclohexanespiro-2′-[2′,3′,6′,7′-tetrahydro-1′H-cyclopenta[d]pyrimidin]-4′(5′H)-one - Shi, Daxin (International Union of Crystallography, 2009)
The title compound, C(12)H(18)N(2)O, was synthesized by the reaction of cyclohexanone and 2-aminocyclopent-1-enecarbonitrile. In the molecule of the title compound, the six-carbon ring displays a chair conformation, the six-membered 1,3-diaza ring and the cyclopentene ring both assume envelope conformations. Supramolecular aggregation is achieved by N—H⋯O hydrogen bonds.